PEDAGOGICAL VIEWS OF THE JADID ENLIGHTENERS - Saitqulova , Mehriniso; Qobilova , Nilguna (Journal of Pedagogical and Philological Research, 2026)
This article analyzes the pedagogical views of the Jadid enlighteners. The Jadids are known as thinkers who introduced innovations in the field of education and upbringing in their time while striving to preserve national values. Their pedagogical ideas were primarily formed on the basis of science, culture, and moral education. The article examines the teaching methods, curricula, and innovative approaches of the Jadid enlighteners in the educational process. Furthermore, their thoughts emphasize the significance of human education, national identity, and modern knowledge. The pedagogical views of the Jadids remain important for introducing innovations into the education system today, just as they were in their own era. This article is aimed at studying the pedagogical heritage of the Jadid enlighteners and assessing its impact on modern education.